Facile SERS substrates from Ag nanostructures chemically synthesized on glass surfaces - Mazur, N.V.; Kapush, O.A.; Isaeva, O.F.; Budzulyak, S.I.; Buziashvili, A.Yu.; Pirko, Y.V.; Skoryk M.А.; Yemets, A.I.; Hreshchuk, O.M.; Yukhymchuk, V.; et al. (Physics and Chemistry of Solid State, 2023)
A quick one-step fabrication of efficient SERS substrates by a modified approach based on a silver-mirror reaction (using Tollens’ reagent) is reported. Commercially available microscope slides or cover glass (coverslips) were used as-received, without special surface treatment. In contrast to the commonly used two-step process, the composition of the Tollens reagent was modified to use a single-step process. The obtained rather homogeneous films of densely packed nanoislands are promising for application as substrates for Surface-Enhanced Raman Scattering (SERS), as demonstrated by several different kinds of molecules as analytes. In particular, the achieved level of detection of a standard dye analyte, down to 10-14 M of Rhodamine 6G, is in the range of best values reported in the literature. Low concentrations of some biomolecules are also detected, such as lysozyme (10-4 M), adenine (10-4 M), and salicylic acid (10-5 M). For some analytes, stronger SERS was observed in the drop, and for others after the solvent was dried. The possible reasons for this effect are described. By applying thermal annealing in the inert gas atmosphere, the Ag film morphology can be partially converted into a coral-like 3D structure that may be advantageous for the localization of the analyte in the “hot spots” and allow additional spectral tunability of the plasmon resonance.